2015
DOI: 10.3390/toxins7062306
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Toxicity of Shiga Toxin (Stx) Type 2c in Mice Compared to Stx2d Is Associated with Instability of Stx2c Holotoxin

Abstract: Shiga toxin (Stx) is an AB5 ribotoxin made by Stx-producing Escherichia coli (STEC). These organisms cause diarrhea, hemorrhagic colitis and the hemolytic uremic syndrome. STEC make two types of Stxs, Stx1 and/or Stx2. Stx2 has one prototype (a) and six subtypes (b–g), but only STEC that make Stx2a, and/or Stx2c, or Stx2d are associated with severe disease. However, Stx2c is about 10-fold less toxic than Stx2d in vivo despite only two amino acid differences in the A subunit at positions 291 and 297. We made mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Isolates encoding stx 2a, the Shiga toxin subtype with the highest cytotoxic potential [14] and classically associated with the risk of HUS, were involved in approximately 85% of HUS cases. stx 2c, although of comparatively lower cytotoxicity and higher heat lability [15], was involved in over 30% of cases of HUS, not all of them justifiable by the concomitant presence of other Shiga toxin subtypes. No cases of HUS were documented among patients infected with the stx 1a stx 2a stx 2c genotype, despite the combination of three different toxins, and those infected with the stx 1a stx 2a genotype isolates were statistically less likely to develop HUS, regardless of the presence of stx 2a.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates encoding stx 2a, the Shiga toxin subtype with the highest cytotoxic potential [14] and classically associated with the risk of HUS, were involved in approximately 85% of HUS cases. stx 2c, although of comparatively lower cytotoxicity and higher heat lability [15], was involved in over 30% of cases of HUS, not all of them justifiable by the concomitant presence of other Shiga toxin subtypes. No cases of HUS were documented among patients infected with the stx 1a stx 2a stx 2c genotype, despite the combination of three different toxins, and those infected with the stx 1a stx 2a genotype isolates were statistically less likely to develop HUS, regardless of the presence of stx 2a.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of developing HUS is increased for children under 10 years age and in patients of any age who develop leukocytosis, experience treatment delays, or receive antibiotics and/or anti-motility agents (Tarr et al, 2005). Although the presence of the locus of enterocyte effacement (LEE) in an STEC isolate, the production of specific Stx subtypes, and E. coli O157:H7 clade classification have been associated with STEC that cause severe human disease (Manning et al, 2008;Neupane et al, 2011;Amigo et al, 2015;Bunger et al, 2015), no other pathogen-specific factors have been identified that can be used to predict the severity of STEC related disease. The focus of this study was to determine whether factors, such as stx-subtype, Stx protein levels, stx-phage insertion sites, and virulence of O157:H7 clinical isolates in a mouse model correlated with disease presentation in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Stx2, on the other hand, is composed of a diverse and heterogeneous group of subtypes, from Stx2a to Stx2h (17)(18)(19). These subtypes differ in potency and species specificity, with Stx2a, Stx2c, and Stx2d linked to severe human illness (20)(21)(22)(23)(24). Stx2a is associated with more severe infections than the other Stx2 subtypes or Stx1a (6,21,(25)(26)(27).…”
mentioning
confidence: 99%